THE ENGLISH LANGUAGE LEARNING AS A PROCESS OF SOCIALISATION - Shestopalova, I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article is devoted to the problem of socialization of an individual in the process of studying a foreign language, which is a part of multicultural education and is considered as an important tool for a person’s adaptation in a multicultural society. The leading idea of the article is the assertion that foreign language as a discipline has a huge socializing potential, as in the process of studying a foreign language, not only in terms of the active development of inherent capabilities, abilities, initiative, independence, take place, but also, in terms of assimilating and activating the generally accepted in a society socio-cultural rules and moral norms, which play a crucial role in the process of socialization. Since the main goal of the educational process in foreign languages is the formation of high communicative skills, its contribution to the process of socialization of a person is indisputable. In this sense, the following characteristics of the learning process in a foreign language are important: the focus on communication, respect for the identity and culture of other people, the focus on social activities, the acquisition of social experience in solving life and social problems, and the creation of its own system of life priorities. The communicative method of teaching foreign languages is based on the fact that the learning process is a model of communication. The learning process in foreign languages is based on the linguistic partnership, creative collaboration, constant motivation of communication, based on a combination of such interconnected factors as activity, creativity, autonomy, individualization, which contribute to the intensification of cognitive and educational processes. That is, organization of training in the form of communication is the main methodological task of a modern teacher of foreign languages. It is this specificity of the discipline "foreign language" that is capable of effective implementing educational socialization, helping to complete the formation of the students' ability to communicate, co-exist and cooperate in the professional activities of people of different ethnic groups, the formation of a rich experience of social and cultural communication, which is a solid base for the involvement of learners to the global values of civilization.
Keywords: socialization; foreign language; multicultural education; polycultural person; professional socialization